What is Socioeconomics? An Overview of Theories, Methods, and Themes in the Field. Issue 1 (2nd January 2017) - Hellmich, Simon Niklas
Abstract : The term socioeconomics is widely used, even though it is often connoted to quite divergent understandings about what it actually describes. It sometimes appears as an umbrella term for a range of quite successful but diverse and occasionally antagonistic approaches that cannot easily be combined. Sometimes it is applied to rather specific scientific endeavors. This paper is not conceptual, i.e., it concludes with some moderate considerations about optional ways to advance a consolidation of socioeconomics only. In first instance, it is intended to provide some orientation in the diverse field and discusses distinctions that can be made between major theoretical and methodological currents, subject areas, and understandings of the purpose of socioeconomics.